Efektivitas Media TikTok Berbasis Model Discovery Learning terhadap Peningkatan Keterampilan Menulis Teks Eksposisi pada Siswa Kelas X MA Al-Falah Sukabumi - Eriska Febrianty; Djeje Djeje; Rifafida Rahmatillah; Unus Unus; Ikhsan Ikhsan; Aan Hasanah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Digital media such as TikTok has become a significant innovation in teaching expository texts in the digital era. However, many students still struggle to recognize the structure and language features of expository texts, affecting the quality of their writing. This study aims to analyze the implementation of TikTok as a learning media based on Discovery Learning to improve expository writing skills among tenth-grade students of MA Al-Falah Sukabumi. The research employed a pretest-posttest control group design with data collection techniques including tests (pretest and posttest) and non-test methods (questionnaires and observations). The subjects consisted of 36 students break into experimental and control groups. The finding showed a significant improvement in the writing skills of the experimental group. Furthermore, 87% of students reported that TikTok made the learning process more engaging and easier to rcognize. In conclusion, TikTok is an effective innovation for Discovery Learning-based teaching to enhance students' expository writing skills.